2021
DOI: 10.1039/d1ob01529j
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Bis-perfluoroalkylations of alkenes and alkynes with perfluorocarboxylic anhydridesviathe formation of perfluoroalkylcopper intermediates

Abstract: 1,2-Bis-perfluoroalkylations of alkenes/alkynes with perfluorocarboxylic anhydrides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In 2021, Sodeoka and colleagues reported the first bisperfluoroalkylation of alkynes (and alkenes) toward the construction of bisperfluoroalkylated alkenes (and alkanes). In this work, a mixture of perfluoroalkyl carboxylic anhydrides, urea/H 2 O 2 , and [Cu(CH 3 CN) 4 ]PF 6 as the catalyst in the presence of the alkyne (or alkene) afforded the respective bisperfluoroalkylated alkenes (or 1,2-bisperfluoroalkylated alkanes from alkenes).…”
Section: Formation Of C(sp 2 )–Rf Bonds: Syntheses Of Perfluoroalkyl-...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Sodeoka and colleagues reported the first bisperfluoroalkylation of alkynes (and alkenes) toward the construction of bisperfluoroalkylated alkenes (and alkanes). In this work, a mixture of perfluoroalkyl carboxylic anhydrides, urea/H 2 O 2 , and [Cu(CH 3 CN) 4 ]PF 6 as the catalyst in the presence of the alkyne (or alkene) afforded the respective bisperfluoroalkylated alkenes (or 1,2-bisperfluoroalkylated alkanes from alkenes).…”
Section: Formation Of C(sp 2 )–Rf Bonds: Syntheses Of Perfluoroalkyl-...mentioning
confidence: 99%
“…Several perfluoroalkylation reagents have been developed to build perfluoroalkylated compounds for diverse applications in organic syntheses, materials sciences, and medicinal chemistry . For example, sodium perfluoroalkylsulfinates (R F SO 2 Na), perfluoroalkylsulfonyl chlorides (R F SO 2 Cl), S -(fluoroalkyl)­diphenylsulfonium salts, perfluoroalkyl carboxylic acids, TMSC n F 2 n +1 , perfluoroacid anhydrides, R F -hypervalent iodine reagents, and perfluoroalkyl halides R F X. , The latter, perfluoroalkyl halides (R F X), are more widely employed compared to other reagents due to their commercial availability, laboratory stability, and convenience in operation. Particularly, radical protocols employing perfluoroalkyl iodides R F –I as radical precursors have been extensively studied .…”
Section: Introductionmentioning
confidence: 99%
“…Last year, the copper-mediated synthesis of diverse bisperfluoroalkylated derivatives from alkenes with perfluorcarboxylic anhydrides has been published by Sodeoka [48] et al The method was extended for the double functionalization of alkynes as well providing the appropriate tetrasubstituted alkenes in acceptable yields (Scheme 45). Mechanistic investigations revealed that the bistrifluormethylation reaction proceeds via the formation of a vinyl radical, in a similar manner as proposed previously by Cook.…”
Section: Alkyne Functionalizationmentioning
confidence: 99%
“…In the last year, Sodeoka [48] realized the copper‐mediated synthesis of diverse bisperfluoroalkylated derivatives in moderate to good yields in the reaction of alkenes with perfluorocarboxylic anhydrides in the presence of H 2 O 2 (Scheme 40). Mechanistic investigations revealed that the key step in this reaction is the formation of a stable perfluoroalkylcopper intermediate achieved with the aid of a bipyridyl ligand.…”
Section: Alkyltrifluoromethylation Reactionsmentioning
confidence: 99%
“…Finally, the reductive elimination of VI leads to the trisubstituted alkenes 4 – 42 and regenerates the Cu I L3 complex I for the next catalytic cycle. The high anti -stereoselectivity of the reaction is likely depending on the relative stability of the intermediate VI , where the sterically demanding alkyl group is anti to the large Ar′Cu III L3 group …”
mentioning
confidence: 99%